Not a Rolling Stone: On Dragging a Stone Weight-Anchor on the Seabed - Yoav Me-Bar; Ayelet Miller; Baruch Ephraim Karlin; Deborah Cvikel (Journal of Marine Science and Engineering, 2024)
The force required to drag a stone anchor over several types of surfaces was measured, recorded, and analyzed. It was found that the force involved in the movement of the anchor over the various surfaces cannot be described just by the sliding solids theory, but it involves several additional physical processes, such as increasing the sand shear strength by the pressure the anchor applies on the sand under it; the sinking of the anchor into the saturated sand; shearing the sand in front of the moving anchor and accelerating it to the velocity of the anchor; accumulating sand in front of the anchor, thus adding to the pulled mass; and moving some of the accumulated sand sideways. In many instances, the beginning of the anchor movement involves the liquefaction of the sand under it, thus enabling the relatively easier sliding of the anchor. In addition, movement over rocky surfaces, encountering the irregularities that abound on such surfaces, also differs from classic sliding friction theory. In several situations, the use of an effective coefficient of friction, combining all the processes, can serve to obtain approximate values of the required forces.